PENGARUH AKTIVITAS FISIK TERHADAP KEJADIAN GIZI LEBIH PADA REMAJA DI MASA PANDEMI COVID-19 - Sellia Juwita; Sara Herlina; Siti Qomariah; Wiwi Sartika (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
Overnutrition is a condition where there is an increase in body weight caused by the accumulation of body fat. More nutrition can be found in every age group such as adults, children and adolescents. During the COVID-19 pandemic, teenagers experienced changes in their physical activity due to social restrictions. Decreased physical activity during the pandemic results in decreased organ system work in fighting viruses and excessive intake with decreased physical activity can lead to weight gain. This study aims to examine the effect of physical activity on the incidence of overnutrition in adolescents during the COVID-19 pandemic. The research method uses an analytical survey with a cross-sectional approach, this research was conducted online in Pekanbaru City. The sample in this study were teenagers who were in the city of Pekanbaru with a random sampling technique with a sample of 335 people. The results of the univariate analysis showed that 208 people (62.1%) had moderate physical activity and 127 people (37.9%) had light activity, and the results of the bivariate test showed that there was an effect of physical activity on the incidence of overweight with P value < 0, 05 (P-value 0.000). It can be concluded that activity affects weight gain or the incidence of overnutrition in adolescents in Pekanbaru City.